Pesquisa na Universidade Federal do Pampa (UNIPAMPA): proposição de uma coordenadoria de gestão de projetos - Palmeira, Eduardo Mauch (2017)
The research project's management at UNIPAMPA is currently a responsibility of its Research Department (Pró-Reitoria de Pesquisa), through the Monitoring and Execution Projects Office (NEAP), which is in charge of monitoring and executing the equipment and expenditure material purchasing to the use of researcher-professors granted with internal and public calls. The key point of this work is to propose a management model for research at Universidade Federal do Pampa, based on the remodeling of a Project's Management Board. The research that took place can be classified as: exploratory, case study and qualitative/quantitative. It was developed at Universidade Federal do Pampa, at the research department. In order to proceed the data collection, semi structured interviews and surveys were applied. The results' analysis conveyed an identification of the researcher-professors profiles, as well as their knowledge on calls for research granting, their awareness about the accountability process, and also to suggest improvements towards a board's constitution. Since that, aspects needed to improve the management processes were identified, through the board and its sectors. Thus, the aim here is to improve not only the research projects management process, but also the search for funding and accountability, leading to a better use of public resources in research projects. As a contribution, the approach of this work is intended to advance the research management process used by universities and federal institutes in Brazil, providing, in this sense, more subsidies to the managers. Thus, the need for research projects management board, focusing on the optimization of the already existing flows.